STUDENT ACHIEVEMENT AND ITS MEASUREMENT. - Oehler, Christian (The Accounting Review, 1943)
In this article the author focuses on the problem of evaluating the progress and achievement of students who take courses in business subjects in collegiate schools of business. The author remarks that too little attention is given to the subject, and yet, no matter how carefully the curriculum may have been planned, if the instructor errs in the evaluation of the achievements of any student by grading him at or above the passing mark when such a mark is not really deserved and earned, an injury has been done to the student, to the college, and to the business community in which the student will later seek employment. Many instructors base their grades solely upon the proportion of the subject matter of the course that the students give evidence of having learned. Students regard the grades they receive as evidence of their attainments. If their grades are high, they rightly consider that they have done well, if low, they consider that something is wrong. It is very important that the instructor, before grading the students at 90, should take into consideration everything that is necessary to enable him to do well in his first employment.